The Influence of Work Environment and Compensation on Employee Performance (MSMEs) at Ibu Nur's Jamblang Rice Stall, Cirebon - Afnan Nindya Wiyanata; Vida Nova Salsabila; Nevasa Cobita; Eteh Resa Asyifa (Sean Institute, 2026)
Employee performance is an important factor that determines the success of a business, including in the micro business sector such as Warung Nasi Jamblang Ibu Nur. To achieve optimal performance, support from various factors is needed, including compensation and work environment. These two factors play a role in shaping employee motivation, satisfaction, and productivity. The research method used is a quantitative method with a survey approach. Data collection was conducted by distributing questionnaires to 30 respondents who were employees of Warung Nasi Jamblang Ibu Nur. The data analysis techniques used included validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, t-testing, F-testing, and coefficient of determination (R²) analysis. The results showed that compensation and work environment had a positive and significant effect on employee performance. This means that the better the compensation provided and the more conducive the work environment created, the higher the performance produced by employees. Thus, management is expected to continue to pay attention to the compensation system and work environment conditions so that employee performance can continue to improve optimally. This study aims to strengthen empirical evidence that fair compensation and a conducive work environment can improve employee performance.